(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
At the present time observing various types of concepts is very cruial and essential in linguistics. Figurative component of concept “Sin”correlates with perceptive and cognitive parts of human being. Perception represents linguistic embodiment of examined phenomenon. The interconnection of verbal and non-verbal means of communication in the speech of a certain society, the theory of non-verbal communication comes into close contact with linguacultural studies and paralinguistics are investigated.